Partnerships in transition: the case of the EU and middle-income countries (MICs). Issue 6 (17th August 2016) - Pilke, Riina
ABSTRACT: The EU has introduced a differentiated approach to development cooperation by reducing financial support for countries graduating to middle-income status from development cooperation. Differentiation will likely be applied in additional countries in the next budget cycle; as such, the way the EU organises differentiation makes for an important pilot case. This article reviews the factors that led to the graduation of certain countries and how this matches with the EU's aspirations to policy coherence for development. The analysis concludes that ambiguous differentiation policy horizontally led to vertical incoherencies in the ways policy objectives are conveyed to financial instruments, and how they subsequently facilitate programming.